The effect of Moringa oleifera L. leaf extract supplementation on the chemical and sensory quality of beef patties cooked to a well-done level - Kartikasari, Lilik Retna; Bayu Setya Hertanto; Farough Heidar Barido; Winny Swastike; Adi Magna Patriadi Nuhriawangsa (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aimed to evaluate the effect of Moringa oleifera L. leaf extract supplementation on the chemical composition and sensory quality of beef patties cooked to a well-done level. This study used a completely randomized design (CRD) in one direction withfive treatments and five replications. The research treatments included the supplementation of Moringa oleifera L. leaf flour extract (MOE) 0% (P0), 1% (P1), 2% (P2), 3% (P3), and 4% (P4). The variables observed included water content, fat, protein, collagen, and sensory attributes. A 15-cm line scale was used to evaluate the intensity of the attributes tested on beef patties by 30 semi-trained panelists. Chemical and organoleptic quality test data were analyzed using Analysis of Variance. If the treatments had a significant effect, then the analysis was continued using the Tukey Test. The results showed that the addition of Moringa leaf flour extract had a very significant effect (P<0.05) on the chemical quality of beef patties (water, fat, and protein content). The use of Moringa oleifera L. leaf extract at the 2% level produces higher protein and fat levels than the use of 4%. Adding MOE up to 4% can increase the intensity of beef patties' color, aroma, and tenderness (P<0.05). The supplementation of Moringa oleifera L. leaf flour extract at the 2% level can produce beef patties with relatively high protein and fat content and can maintain sensory quality.